Acute symptomatic neonatal seizures in preterm neonates: etiologies and treatments. Issue 3 (June 2018) - Pisani, Francesco; Spagnoli, Carlotta
Abstract: Acute symptomatic neonatal seizures in preterm newborns are a relevant clinical challenge due to the presence of many knowledge gaps. Etiology-wise, acute symptomatic seizures have an age-specific epidemiology, with intraventricular hemorrhage and its complications representing the first cause in extremely and very preterm neonates, whereas other etiologies have similar occurrence rates as in full-term infants. Specific treatment strategies for the premature neonates are not yet available. Studies suggest a similarly low response rate with even more unfavorable prognosis than in full-term infants. Pharmacodynamic and pharmacokinetic changes are likely under way during the preterm period, with the potential to affect both effectiveness and safety of antiepileptic drugs in these patients. However, due to the lack of clear evidence to guide prioritization of second-line drugs, off-label medications are frequently indicated by review papers and flow-charts, and are prescribed in clinical practice. We therefore conclude by exploring potential future lines of research.